2020
DOI: 10.1038/s41386-020-0606-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower brain fatty acid amide hydrolase in treatment-seeking patients with alcohol use disorder: a positron emission tomography study with [C-11]CURB

Abstract: The endocannabinoid enzyme, fatty acid amide hydrolase (FAAH), has been proposed as a therapeutic target for alcohol use disorder (AUD) and co-morbid psychiatric illnesses. Investigating this target in the living human brain and its relationship to clinical outcome is a critical step of informed drug development. Our objective was to establish whether brain FAAH levels are low in individuals with AUD and related to drinking behavior. In this pilot study, treatment-seeking patients with AUD completed two PET sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 45 publications
(59 reference statements)
2
18
0
Order By: Relevance
“…However, none of the other regions sampled had significantly lower [ 11 C]CURB λ k 3 values. Lower amygdala FAAH expression is consistent with decreased FAAH expression observed across the brain in other externalizing conditions, such as alcohol and substance use disorders 37 , 39 . Our study was likely underpowered to detect differences in all ROIs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, none of the other regions sampled had significantly lower [ 11 C]CURB λ k 3 values. Lower amygdala FAAH expression is consistent with decreased FAAH expression observed across the brain in other externalizing conditions, such as alcohol and substance use disorders 37 , 39 . Our study was likely underpowered to detect differences in all ROIs.…”
Section: Discussionsupporting
confidence: 74%
“…None of the participants screened positive for drugs of abuse, including cannabis. Healthy participants (e.g., no ASPD, no SCZ) and community participants with SCZ had previously participated in other PET experiments 36 , 37 . Groups did not differ in terms of age, ethnicity, body mass index, or number of participants with the C385A FAAH genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, a recent study in adult humans of Caucasian/European ancestry with AUD reported that individuals with the AC or AA genotype engaged in significantly more drinking days and heavy drinking episodes, and had greater self-reported alcohol use severity compared to CC homozygotes (Sloan et al, 2017). Consistent with this finding, low FAAH brain levels, as measured using positron emission tomography, were associated with increased alcohol consumption in a sample of treatment-seeking individuals with AUD (Best et al, 2020). Together, these findings suggest that low FAAH activity may be related to increased alcohol consumption and vulnerability for AUD, though the mechanism by which this might occur requires further investigation.…”
mentioning
confidence: 68%
“…Participants were recruited from community and university settings in Toronto, Canada, for participation in 1 of 2 larger studies investigating the risk for AUD in youth (Best et al, 2020; Hendershot et al, 2017). To be eligible for inclusion in either of the 2 larger studies, participants were at least 18 years of age, reported at least 1 occurrence of HED in the previous 30 days, no current medication or medical condition contraindicating alcohol consumption and no current diagnosis or treatment of a psychiatric condition or substance use disorder, as assessed by the Structured Clinical Interview for DSM‐IV or the Mini International Neuropsychiatric Interview.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a PET scan study for a FAAH radiotracer was conducted in the brain of AUD patients during early abstinence. It showed transiently reduced FAAH levels, while its substrates AEA, OEA, and N- docosahexaenoyl ethanolamide (DEA) were elevated in the plasma (Best et al, 2020 ). Low FAAH levels are related to drinking behaviors and increased preference for alcohol, as demonstrated in several studies using animal models with genetic deletions (Basavarajappa et al, 2006 ; Blednov et al, 2006 ; Vinod et al, 2008 ; Pavón et al, 2018 ); or following pharmacological manipulation (Zhou et al, 2017 ).…”
Section: Role Of Naes and Pparα In Alcohol Use Disordermentioning
confidence: 99%